1999
DOI: 10.1002/(sici)1097-4628(19991107)74:6<1355::aid-app5>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

A novel, efficient procedure for acylation of cellulose under homogeneous solution conditions

Abstract: Commercially available cellulose (Avicel PH101) was successfully acylated under homogeneous solution conditions by the following novel procedure: 2.0 g of cellulose and 5.0 g of LiCl were introduced into a glass reactor, magnetic stirring was started, the pressure was reduced to 2 mmHg, the temperature was raised to 110°C in 30 min, and the reactor was kept under these conditions for another 30 min. N,NDimethylacetamide, 60 mL, was introduced, atmospheric pressure was restored, and the temperature was raised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 26 publications
(35 reference statements)
3
33
0
2
Order By: Relevance
“…sugarcane bagasse) [2][3][4][6][7][8][9][10] mainly aiming at obtaining acetates. Cellulose derivatives, as esters, are largely industrially produced in heterogeneous medium.…”
supporting
confidence: 92%
“…sugarcane bagasse) [2][3][4][6][7][8][9][10] mainly aiming at obtaining acetates. Cellulose derivatives, as esters, are largely industrially produced in heterogeneous medium.…”
supporting
confidence: 92%
“…When the reactions proceed in homogeneous solutions, the regioselectivity depends on the reactivity differences among the free hydroxyl groups on the cellulose molecules [152], not by their accessibility [153].…”
Section: Industrial Cellulose Derivative Production Methodsmentioning
confidence: 99%
“…The reactivity of OH in the C6 position is favored, when compared to C2 and C3, because this group is the least sterically hindered of the AGU unity [49] . Acetates samples here described were prepared in DMAc/LiCl following previous study [11] , and the order of reactivity observed for all samples was C6>>C2>C3, confirming the higher reactivity of C6OH.…”
Section: Characterization Of Cellulose Acetatesmentioning
confidence: 99%